ANALISIS KEPERCAYAAN DIRI SISWA KELAS X SMA NEGERI 1 BENAI - Ningsih, Fitri; Umari, Tri; Rosmawati, Rosmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This study entitled "Analysis of Self-Esteem Class X SMAN 1 Benai" As for the melatarbelakgi this study was low self-esteem class X SMA Negeri 1 Benai. This study aims to reveal the confidence of class X SMA Negeri 1 Benai and to find confidence peritem class X SMA Negeri 1 Benai. The benefits of this research is to inform the relevant parties, especially parents and teachers to know the description of students 'self confidence and as information for students in order to increase the confidence of students as well as information and materials research studies to further students' confidence.This research method using descriptive analytic method, a method that aims to obtain a description of a situation or phenomenon, and after the analysis. In this research will be distributing questionnaires to determine the emotional stability of students of class X SMAN 1 Benai in the school year 2015/2016, and will be at the analysis of the emotional stability of students - the student through the scale. Based on research data that have authors to conclude sump confidence keapada grade X SMAN 1 Benai with a total of 114 students, it was concluded that the vast majority of confidence in class X SMA Negeri 1 Benai categorized under the category of "low".Keywords Self-Esteem, Analysis